2020
DOI: 10.1002/chem.201904725
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Environments as a Tool to Preserve Desired Output in a Chemical Reaction Network

Abstract: Currente fforts to design functional molecular systems have overlooked the importance of coupling out-ofequilibrium behaviour with changes in the environment. Here, the authors use an oscillating reaction network and demonstrate that the application of environmental forcing, in the form of periodic changes in temperature and in the inflow of the concentrationo fo ne of the network components, removes the dependency of the periodicity of this network on temperature or flow rates and enforces as table periodicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…The universality of this broadening, in that it occurs irrespective of whether the temperature is raised/lowered or whether flow rates are increased/ decreased, demonstrates the increase in FWHM can act as an early warning signal. In addition to the effect of temperature on the FWHM, an examination of some of our previously reported experimental results 24 confirmed that as the flow rate is changed and the system approaches the edge of the sustained oscillation region an increase in FWHM occurred (Fig. S6, ESI †).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The universality of this broadening, in that it occurs irrespective of whether the temperature is raised/lowered or whether flow rates are increased/ decreased, demonstrates the increase in FWHM can act as an early warning signal. In addition to the effect of temperature on the FWHM, an examination of some of our previously reported experimental results 24 confirmed that as the flow rate is changed and the system approaches the edge of the sustained oscillation region an increase in FWHM occurred (Fig. S6, ESI †).…”
supporting
confidence: 63%
“…We complemented the experimental data by modelling the effect of perturbations upon the recovery time using the previously reported temperature dependent rate equations (see ESI † Section 4 for details). 24 A comparison between the experimental and modelled results showed reasonable agreement (Fig. 2c).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…To induce a pH change, the autocatalytic reaction between urea and urease was developed by Taylor et al [55][56][57] and also used by Walther et al 58,59 and other research groups. 16,[60][61][62][63] Under aqueous conditions, urea reacts with urease to produce ammonia, which is responsible for the increase of the pH of the medium. [64][65][66][67][68] The reaction itself is highly dependent on the initial reaction conditions such as pH and the reagent concentrations, 57,64,65 which enables us to exercise precise control over the rate of pH change and subsequent transitions between the energy states.…”
Section: Resultsmentioning
confidence: 99%
“… 4 8 Previous work has shown the development of small network motifs 9 by autocatalysis and delayed inhibition, 10 photochemical control of oscillations by reversible photoinhibitors, 11 coupling to DNA-based circuits, 12 logic-gate responses, 13 pattern-formation, 14 adaptive responses to environmental perturbations, 15 and coupling to dynamic environments. 16 While these networks can show complex behavior, such as oscillations and adaptation, scaling up their size toward metabolic scales remains a significant challenge. To construct complex, yet functional ERNs, estimating the mechanisms and kinetics of the enzymatic reactions in these systems is essential in order to reliably predict the relevant experimental regimes in which a desired functional output will be observed.…”
Section: Introductionmentioning
confidence: 99%